Variabilidade Espacial e Temporal das Características Limnológicas dos Reservatórios Santa Cruz e Umari, Semiárido do Rio Grande do Norte, Brasil - Santos, Rafson Varela dos (Universidade Federal Rural do Semi-Árido, 2014)
The construction of reservoirs has been adopted as a strategic measure to overcome water shortages and cope with the increase of the multiple uses of this resource. Despite its social importance, the impounding of a lotic ecosystem tends to break possible longitudinal gradients, resulting in biotic and abiotic change both downstream and upstream of the reservoir. In this context, this work sought: (i) to describe the morphometric parameters of the Santa Cruz and Umari reservoirs in the semi-arid region of Rio Grande do Norte; (ii) to spatially and temporally assess the limnological characteristics of these water reservoirs. Bathymetric surveying was carried out in December 2012, with the aid of an ecobathymeter enhanced via DGPS, utilizing horizontal WGS 84 datum and the UTM coordinate system. Four samplings were extracted from the surface, the center and the bottom of the water column (integrated samples) in May, August and November 2012 and February 2013, so that limnological variables could be assessed. With the aid of a multiparameter probe, the following variables were measured in loco: pH, water temperature, electrical conductivity, total dissolved solids, turbidity and dissolved oxygen, and, via utilization of the Secchi disk, water transparence. In the Laboratory of Limnology and Water Quality of the Universidade Federal Rural do Semi-Árido, the concentration of total N, total P, ammoniacal nitrogen, nitrite N, nitrate N and Chlorophyll a was measured. Regression analyses were conducted so as to identify possible relationships between the limnological variables and the distance from the dam, and Principal Component Analyses were carried out in order to observe a spatial pattern of the points sampled during the temporal variation and gather the data concerning the sampling stations (longitudinal variation) and the collections (temporal variation). Bathymetry in Santa Cruz was based on a total of 35.971 point pairs (depth and location) and in Umari, on a total of 26.575. The Santa Cruz reservoir was verified to have a maximum length of 15.984m, average water depth of 13m and maximum depth of 38m. As for the Umari reservoir, maximum length, average depth and maximum depth were confirmed to be 14.227m, 8m and 28m, respectively. In what concerns the storage volume, accentuated differences between the two reservoirs were recorded: 295.858.761m3 in Santa Cruz and 114.866.034m3 in Umari. Despite bearing a smaller volume, Umari presented a larger perimeter area (110.887,26 m). Both reservoirs showed a shallow relative depth which could lead to thermal instability and, consequently, a mixture of the water masses. The results of the PCA showed a spatial pattern in which, as the water ran closer to the influence zone of affluent rivers, there were higher figures of temperature, electrical conductivity, turbidity, total dissolved solids, total P, total N, and Chlorophyll a. However, it could not be verified, in either reservoir, a clear pattern of temporal variation, likely due to the low rainfall during the entire period of sampling. Finally, the reservoirs proved to be adequate for various uses, abiding to the standards set by the CONAMA resolution nº 357/2005, the average concentrations of limnological variables being considered acceptable for Class 1, with the exception of the concentration of total P in the reservoir of Santa Cruz, which was considered acceptable for Class 2. It was concluded that the classic concept of longitudinal compartmentalization with three evident zones (fluvial, transition and lake) did not apply to the reservoirs in this study; therefore, it was only possible to identify partial compartmentalization: the lake zone, accounting for the larger part of both reservoirs and bearing oligotrophic characteristics, and a reduced fluvial zone, varying between mesotrophic and eutrotrophic
SPATIAL AND TEMPORAL VARIABILITY OF LIMNOLOGICAL CHARACTERISTICS IN THE SANTA CRUZ AND UMARI RESERVOIRS, SEMI-ARID REGION OF RIO GRANDE DO NORTE, BRAZIL
Keywords: Limnological variables; Reservoir; Morphometrics; Spatial-temporal heterogeneity; Semi-arid; Trophic state index; Variáveis limnológicas; Reservatório de água; Morfometria; Heterogeneidade espaço-temporal; Semiárido; Índice de estado trófico; CIENCIAS AGRARIAS::MEDICINA VETERINARIA